In Mapping Digital Jihad: Understanding the Structure and Evolution of al-Qaeda’s Information Ecosystem on the Surface Web - Lakomy, Miron (Perspectives on terrorism, 2024)
This article, which combines social network analysis and open-source intelligence, discusses the functions, structure, and evolution of al-Qaeda’s (AQ) information ecosystem on the surface web in the second half of 2023. It argues that despite preferring Rocket Chat as a primary communication channel, this terrorist organisation developed an extensive and robust propaganda distribution network detectable from the surface web. The pro-AQ ecosystem on this Internet communication layer relied primarily on standalone websites, message boards, and blogs, interconnected with a broad range of file-sharing services and channels on encrypted communication apps. Aside from them, the group manifested limited activity on mainstream social media. In the second half of 2023, the group demonstrated resilience to content takedowns, as most of its key domains used to disseminate propaganda continued to be active under the same or changed URLs. This study shows that, in contrast to the Islamic State, al-Qaeda’s information ecosystem was largely decentralised, which was primarily caused by the differentiated approaches of its branches to maintaining their presence in this environment. The lack of centralisation of AQ’s propaganda distribution network may be considered both an advantage and a disadvantage. On the one hand, it potentially increases its resilience to content takedowns. On the other hand, however, it also demonstrates a lack of coordination between branches, which decreases their media operations’ potential efficiency and reach.